Approximating interior bounded box of 3D character mesh model based on its skeleton and symmetry. Issue 3 (14th August 2017) - Xu, Hanxiang; Guo, Shihui; Yao, Junfeng; Thalmann, Nadia Magnenat
Abstract : Purpose: In the process of robot shell design, it is necessary to match the shape of the input 3D original character mesh model and robot endoskeleton, in order to make the input model fit for robot and avoid collision. So, the purpose of this paper is to find an object of reference, which can be used for the process of shape matching. Design/methodology/approach: In this work, the authors propose an interior bounded box (IBB) approach that derives from oriented bounding box (OBB). This kind of box is inside the closed mesh model. At the same time, it has maximum volume which is aligned with the object axis but is enclosed by all the mesh vertices. Based on the IBB of input mesh model and the OBB of robot endoskeleton, the authors can complete the process of shape matching. In this paper, the authors use an evolutionary algorithm, covariance matrix adaptation evolution strategy (CMA-ES), to approximate the IBB based on skeleton and symmetry of input character mesh model. Findings: Based on the evolutionary algorithm CMA-ES, the optimal position and scale information of IBB can be found. The authors can obtain satisfactory IBB result after this optimization process. The output IBB has maximum volume and is enveloped by the input character mesh model as well. Originality/value: To the best knowledge of the authors, the IBB is first proposed and used in the field of robot shell design. Taking advantage of the IBB, people can quickly obtain a shell model that fit for robot. At the same time, it can avoid collision between shell model and the robot endoskeleton.